PENERAPAN MODEL GDL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK TENTANG MATERI TEKANAN ZAT - Oktavarina, Adelia; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to determine the application of the Guided Discovery Learning (GDL) model in improve students critical thinking skills about substance pressure in SMP Negeri 3 Ketapang. The research method used was an experimental research in the form of a pre-experimental design with a pretest-posttest design model. The data collection technique used was a whole group technique and obtained VIII A class with a total of 34 students. The instrument of this study has 5 description tests. Based on the results of the Wilcoxon statistical test obtained a significant increase with asymp.sig (2-tailed) below 0.05 (0,000 <0.05). The increase in critical thinking skills in each indicator, namely the Indicator states that the results have increased by 9.44. The indicator describes the procedure at 10,80 and the indicator presents an argument of 9,32. The effectiveness of using the Guided Discovery Learning model is 3.92 with a high category according to Cohen's effect size.Â Keywords: Critical Thinking Skill, Explanation Aspect, Guided Discovery Learning,